Immunological Studies of Reactive Oxygen Species Damaged Catalase in Patients with Systemic Lupus Erythematosus: Correlation with Disease Activity Index. (April 2013) - Al-Shobaili, Hani A.; Robaee, Ahmad A. Al; Alzolibani, Abdullateef A.; Rasheed, Zafar
<x xml:space="preserve">Abstract</x> Objectives: This study was undertaken to investigate the status and contribution of oxidized catalase in systemic lupus erythematosus (SLE) and to explore whether oxidized catalase has a role in disease progression. Methods: Catalase (CAT) was modified by reactive oxygen species (ROS). Sera from 50 SLE patients with varying levels of disease activity according to SLE Disease-Activity-Index (SLEDAI) and 45 age- and sex-matched healthy controls were evaluated for antibodies against oxidized CAT. Results: Serum analysis showed significantly higher level of anti-oxidized-CAT-antibodies in SLE patients compared with controls. Interestingly, not only was there an increased number of subjects positive for anti-oxidized-CAT-antibodies, but also the levels of these antibodies were significantly higher among SLE patients, whose SLEDAI scores were ≥10 as compared with lower SLEDAI scores (<10). In addition, significant correlation was observed between the levels of anti-oxidized-CAT-antibodies and SLEDAI score (r = 0.796). Furthermore, sera from SLE patients had lower levels of CAT activity compared with control sera. Conclusions: These findings support an association between oxidized CAT and SLE. The stronger response observed in serum samples from patients with higher SLEDAI scores suggests that oxidized CAT may be a useful biomarker in evaluating the progression of SLE and in elucidating the mechanisms of disease pathogenesis.